2018
DOI: 10.1002/etc.4144
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the behavior, uptake, and toxicity of NM300K silver nanoparticles in Caenorhabditis elegans

Abstract: Using Caenorhabditis elegans as a model organism, we addressed the potential linkage among toxicity of NM300K Ag nanoparticles (AgNPs), their particle size distribution, and the presence of dissolved Ag in the test media. Of the 3 endpoints assessed (growth, fertility, and reproduction), reproduction was the most sensitive, with the 50% effect concentration (EC50) ranging from 0.26 to 0.84 mg Ag L and 0.08 to 0.11 mg Ag L for NM300K and AgNO , respectively. Silver uptake by C. elegans was similar for both form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In the present study, low levels of dissolved Ag were found in the Ag-NPs exposure dispersions shortly after exposure, and the amounts were lower than the measured EC 50 for cytotoxicity of AgNO 3 . Higher amounts of dissolved Ag have been found in other studies using the same Ag-NPs [6,37,54], and the differences may be related to distinct exposure media, different incubation times and sample preparation. However, most Ag + released from the NPs will not remain freely dissolved in the cell culture medium, due to the high ionic strength of cell culture media and presence of halides (0.12 M total dissolved Cl [66]), amino acids and proteins.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present study, low levels of dissolved Ag were found in the Ag-NPs exposure dispersions shortly after exposure, and the amounts were lower than the measured EC 50 for cytotoxicity of AgNO 3 . Higher amounts of dissolved Ag have been found in other studies using the same Ag-NPs [6,37,54], and the differences may be related to distinct exposure media, different incubation times and sample preparation. However, most Ag + released from the NPs will not remain freely dissolved in the cell culture medium, due to the high ionic strength of cell culture media and presence of halides (0.12 M total dissolved Cl [66]), amino acids and proteins.…”
Section: Discussionmentioning
confidence: 58%
“…Medium without NPs was used as control. The samples were transferred to Amicon Ultra centrifugal filter unit tubes (Millipore, product no UFC900324) containing a 3 KDa filter unit [37]. The tubes were preconditioned before use with ultrapure water at 3900 g for 10 min.…”
Section: Analysis Of Silver and Zinc Ions In Np Dispersionsmentioning
confidence: 99%
“…Ag and SiO 2 nanoparticles have been shown to affect locomotion velocity in C. elegans N2, as previously described (Jung et al, 2015). In addition, Ag and SiO 2 have been shown to reduce brood size, according to several studies (Kleiven et al, 2018;Wu et al, 2013;Pluskota et al, 2009). In contrast, we did not observe a significant decrease in brood size to exposure to 10 and 50 µg/ml of TiO 2 nanoparticles, as observed by Wu et al (2013), indicating differences in our conditions, as these authors saw a slight decrease in progeny production when using these nanoparticles in the µg/l concentration range.…”
Section: Sio2mentioning
confidence: 53%
“…These parameters, however, are influenced by surface chemistry and hence reactivity, as well as by the size of the Ag NPs. Kleiven et al (2018) showed high intake, but low retention of ~0.6 to 2% of the NM300K Ag NPs by C. elegans after depuration, indicating negligible levels of cellular internalization of the NM300K Ag Potentially, ionic releases from the particles could result in intracellular uptake of Ag and cause toxic effects. Studies on the dissolution of uncoated NM300K Ag NPs showed time and media composition dependent ionic releases, varying between 0.07 -29 % (Wasmuth et al, 2016, Köser et al, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Since the importance of physicochemical characteristics of Ag NPs in explaining toxic responses has been shown in previous studies (Kleiven et al, 2018), we conducted detailed characterization of the NM300K Ag NPs, prior and post application to the exposure media, as well as monitored changes over time. TEM analysis of stock suspensions showed an average size of 23.2 ± 17.2 nm (mean ± SD, throughout the text) ( Figure S1), which is in good agreement with supplier characteristics.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%